x^2+y^2+18x+2y=-46

x^2+y^2+18x+2y+46=0

Convert the above to the form (x+a)^2 to (y+b)^2 = r^2

so the center will be (-a, -b) and radius is r

so the above equation becomes

x^2+18x+81+y^2+2y+1+46-81-1 =0

(x+9)^2 + (y+1)^2 +46-82 =0

(x+9)^2 + (y+1)^2 -36 =0

(x+9)^2 + (y+1)^2 =36

(x+9)^2 + (y+1)^2 =6^2

So r= 6

so is it (-9, -1), r=6 or (-1,-9), r=6 which one is it?

(-9, -1), r=6

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up